Effect of microcirculatory resistance on coronary blood flow and instantaneous wave-free ratio: A computational study. (November 2020) - Liu, Haipeng; Ou, Shanxing; Liu, Panli; Xu, Yuhang; Gong, Yinglan; Xia, Ling; Leng, Xinyi; Leung, Thomas Wai Hong; Shi, Lin; Zheng, Dingchang
Highlights: Coronary microcirculatory dysfunction could be simulated using computational fluid dynamics. MR variations in a branch with mild stenosis has limited hemodynamic effects on other branches. Increased MR in a highly stenosed branch increases the blood flow and iFR of its cognate branches. Abstract: Background and objective: The instantaneous wave-free ratio (iFR) has been proposed to estimate the hemodynamic severity of atherosclerotic stenosis in coronary arteries. The atherosclerotic stenosis in a proximal coronary artery could change its distal microcirculatory resistance (MR). However, there is a lack of investigation about the effect of MR variation on the blood flow and iFR of stenotic coronary arteries. We aim to investigate the changes of blood flow and iFR caused by distal MR variation. Methods: Four three-dimensional models of coronary arteries were reconstructed from the computed tomography images of two normal cases and two cases with 74.9% and 96.4% (in area) stenoses in a large branch of left anterior descending artery (LAD). Computational fluid dynamics simulation was performed on each model under 6 MR situations: hyperemia as the reference situation, resting when MR was multiplied by 8/3 in all outlet branches, h-one-1.5 and h-one-2 when MR was multiplied by 1.5 and 2.0 in one branch (the stenotic, or the corresponding branch in normal case) of LAD, h-branches-1.5 and h-branches-2 when MR was multiplied by 1.5 and 2.0 in the stenotic/corresponding and its cognate branches. Flow rate and iFR of each outlet branch were then calculated and compared between different MR situations to investigate the effect of MR variation on flow rate and iFR. Results: In the 74.9% stenosed and normal cases, referring to the hyperemia situation, the increase of MR in any branch significantly decreased its flow rate and increased its iFR, with limited effect on the flow rate (<3%) and iFR (<0.01) of other branches. However, in the 96.4% stenosed case, the doubled MR in the stenosed branch (h-one-2) significantly increased the flow rate (>10%) and iFR (>0.05) of its cognate branches. Conclusion: The increase of MR in a normal or mildly stenosed branch of coronary artery decreases its blood flow and increases its iFR, with limited effect on other branches. Whereas, the increase of MR in a severely stenotic large branch could significantly increase the flow velocity and iFR of its cognate branches.